Transaksi Uang Elektronik: Dampaknya terhadap Efektivitas Kebijakan Moneter Indonesia - Norlaila; Anward, Ryan Juminta (PPJP ULM, 2023)
As a new payment instrument, electronic money usage is increasing yearly. This can be seen from the increasing volume and nominal transactions. This study aims to see whether electronic money transactions affect the effectiveness of monetary policy in Indonesia, as seen from economic growth, inflation, interest rates, and money supply. The analytical method used is the Vector Autoregression/ Vector Error Correction Model (VAR/ VECM), using secondary time series data sourced from the Central Bureau of Statistics and Bank Indonesia, observation period 2010M1 to 2021M12. The results show that there is a long-term relationship between the electronic money variable and the monetary policy variable in the VAR model, so the model shifted to VECM. Second, this study finds that an increase in the volume of electronic money transactions positively affects the effectiveness of monetary policy in the long run. Meanwhile, in the long run, an increase in the nominal of electronic money transactions has a varying impact on monetary policy indicators.